Odpowiedzi

2010-02-24T13:38:27+01:00
A) -4x-7-3x+7= -7x


b) x - 2xy+ 1/2x - 1/3xy =
- 2 i 1/3xy + 1 i 1/2 x

c) -x2+y2 - 2x2 - 2y2 = -3x² + y²


d) -x2 + 2x - 3x+ x2 = x


e) 4x + 4-7x - 1/2 = -3x + 3,5


f) -2ab + 12a - 4ab - 16a = -6ab - 4a
10 3 10
2010-02-24T13:42:40+01:00
A) -4x-7-3x+7=-7x
b) x - 2xy+ 1/2x - 1/3xy =1i1/2x-1i2/3xy
c) -x2+y2 - 2x2 - 2y2 =-3x2-y2
d) -x2 + 2x - 3x+ x2 = -x
e) 4x + 4-7x - 1/2 = -3x +3i1/2
f) -2ab + 12a - 4ab - 16a = -4a -6ab
9 3 9
Najlepsza Odpowiedź!
2010-02-24T13:45:39+01:00
A)-4x-7-3x+7=-4x-3x-7+7=-7x
b) x - 2xy+ 1/2x - 1/3xy =x+1/2x-2xy-1/3xy=1 1/2x-2 1/3xy
c) -x2+y2 - 2x2 - 2y2 =-x2-2x2+y2-2y2=-3x2-y2
d) -x2 + 2x - 3x+ x2 =-x2+x2+2x-3x=x
e) 4x + 4-7x - 1/2 =4x-7x+4-1/2=-3x+3 1/2
f) -2ab + 12a - 4ab - 16a =-2ab-4ab+12a-16a=-6ab-4a
29 4 29